The Effect of Organizational Culture and Perceived Organizational Support on Innovative Work Behavior - Cardina, Dica Surya; Negara, Danes Jaya; Irawan, Irawan (Lembaran Ilmu Kependidikan, 2022)
In the current era of bureaucratic reform, the State Civil Apparatus must have positive competitiveness and is required to innovate and develop their competencies in carrying out their duties and responsibilities in order to achieve the best performance for the organization. This requires the full effort and support of the organization by utilizing the organization's internal resources. Therefore, this study aims to determine and analyze the influence of organizational culture and perceived organizational support on innovative work behavior through the mediating role of knowledge sharing at the Supreme Audit Board (BPK) Representative of Central Kalimantan Province. This study uses quantitative methods with data collection through the distribution of questionnaires with a sample of 103 respondents. Data analysis using SEM-PLS with Smart Pls 3.0 tools. The results showed that organizational culture had no significant effect on innovative work behavior, but showed significant results when knowledge sharing mediated the relationship. In addition, the perceived organizational support has a significant effect on innovative work behavior but knowledge sharing cannot mediate the relationship.